A Perspective of Coagulation Dysfunction in Multiple Sclerosis and in Experimental Allergic Encephalomyelitis - Plantone, Domenico; Inglese, Matilde; Salvetti, Marco; Koudriavtseva, Tatiana (Frontiers in Neurology, 2019)
A key role of both coagulation and vascular thrombosis has been reported since the first descriptions of multiple sclerosis (MS). Subsequently, the observation of a close concordance between perivascular fibrin(ogen) deposition and the occurrence of clinical signs in experimental allergic encephalomyelitis (EAE), an animal model of MS, led to numerous investigations focused on the role of thrombin and fibrin(ogen). Indeed, the activation of microglia, resident innate immune cells, occurs early after fibrinogen leakage in the pre-demyelinating lesion stage of EAE and MS. Thrombin has both neuroprotective and pro-apoptotic effects according to its concentration. After exposure to high concentrations of thrombin, astrocytes become reactive and lose their neuroprotective and supportive functions, microglia proliferate, and produce reactive oxygen species, IL-1β, and TNFα. Heparin inhibits the thrombin generation and suppresses EAE. Platelets play an important role too. Indeed, in the acute phase of the disease, they begin the inflammatory response in the central nervous system by producing of IL-1alpha and triggering and amplifying the immune response. Their depletion, on the contrary, ameliorates the course of EAE. Finally, it has been proven that the use of several anticoagulant agents can successfully improve EAE. Altogether, these studies highlight the role of the coagulation pathway in the pathophysiology of MS and suggest possible therapeutic targets that may complement existing treatments.